(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Â Â Â Â Â Â Â Â Â Â Â Durability characteristics of concrete play an imperative role in the performance of the buildings. Concrete despite its versatility is known to have several limitations. It is weak in tension, has limited ductility, shows little resistance to cracking, its permeability to liquids, has poor resistance to sulphate attack and subsequent reinforcementâ€™s corrosion are such restrictions. Research to overcome these limitations led to the development of special concretes like high performance concrete& fibre reinforced concrete. However when fibres are exposed to aggressive environment, rusting takes place and leads to corrosion of fibres. This can be reduced by using stainless steel fibres instead of steel fibre. An experimental study has been taken up to study the impact of various chemicals like sulphates, chlorides, acids and effects of corrosion on concrete. Also the influences of fibres in enhancing the durability characterisitics of concrete under such aggressive environment were studied. This experimental study proves that the Stainless Steel fibre reinforced concrete has several advantages over steel fibre reinforced concrete and has better durability & corrosion resistance.